The milk fat globule size governs a physiological switch for biofilm formation by Bacillus subtilis - Raz, Chen; Paramonov, Margarita Maggie; Shemesh, Moshe; Argov-Argaman, Nurit (Frontiers in Nutrition, 2022)
Milk lipids are organized in the form of milk fat globules (MFG), ranging in size from 0.1-15µm. The MFG size is closely associated with the composition of fatty acids, polar lipids, sphingolipids, cholesterol and the content of the MFG membrane (MFGM). Also, the MFGM integral proteins and glycoconjugates differ in composition and structure between different MFG size groups. These compositional differences may modulate the functionality of the MFG during its contact with microbial cells. We report that the small (2.3µm) MFG facilitates the growth of the Gram-positive bacterium Bacillus subtilis. Besides, a notable induction in biofilm formation was found in the presence of large (7.0µm) MFG. Attempting to distinguish between the role played by the size from that played by the composition of the MFG , we normalized phospholipid composition between treatments. We found that adjusting the phosphatidylethanolamine (PE) level to the concentration found in the small MFG, increased growth but suppressed biofilm formation in the presence of large MFG. Whereas, the same adjusting protocol used for the phosphatidylinositol (PI) did not exert a similar effect. We suggest that the content of MFGM , affected by MFG size, govern the ability of B. subtilis to utilize nutrients from milk fat; this process subsequently affects the bacterial decision-making towards biofilm formation.